Species diversity and the spread of invasive fish in the Upper Bengawan Solo River, Central Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Haqqi MRA, Sholichah DM, Armando MF, Sani MF, Aprianto MK, Dewangga A, Yap CK, Dadiono MS, Setyawan AD. 2024. Species diversity and the spread of invasive fish in the Upper Bengawan Solo River, Central Java, Indonesia. Biodiversitas 25: 4000-4010. Bengawan Solo is the largest and longest river in Java, Indonesia, and has a major role in supporting the life of communities around it. To understand the quality of the Bengawan Solo River environment, the study can be done from physical, chemical, and biological aspects. This research was carried out to inventory the species and the spread of invasive fish found in the Upper Bengawan Solo River, Central Java, Indonesia. This research was conducted from November to December 2023 and settled on 5 sampling stations located on main body of Bengawan Solo River, including (i) northern spillway of Gajah Mungkur Reservoir, Wonogiri, (ii) Colo Reservoir, Sukoharjo, (iii) Demangan Floodgate, Surakarta, (iv) Tlumpuk, Karanganyar, and (v) Jati, Sragen. Data collection was performed using Visual Encounter Survey (VES) and direct catch with several fishing tools, collected species identified using iNaturalist, and several books such as Jenis Ikan Introduksi dan Invasif Asing di Indonesia, Ikan Air Tawar di Ekosistem Bukit Tigapuluh, Ensiklopedia Populer Ikan Air Tawar, and Baku Saku Pengolah Data Jenis Ikan. Identification also carried out by interviewing local people at study area location to match out vernacular names. The results showed 20 species of fish from 12 families were found, dominated by Cyprinidae. The most fish captured is tilapia (Oreochromis niloticus), which can be obtained from all the sampling stations. A species with high conservation status according to IUCN Red List was also found, namely Rasbora lateristriata with Vulnerable (VU) status. As many as 6 species discovered were categorized as invasive, including snakehead fish (Channa striata), red devil fish (Amphilophus citrinellus), tilapia (O. niloticus), catfish (Clarias gariepinus), sailfin catfish (Pterygoplichthys pardalis), and guppy (Poecilia reticulata). Their invasive characteristics are usually due to their predatory trait, well adaptability, and high population. The introduction of invasive fish in the Upper Bengawan Solo River was caused by several reasons, such as intentional release for stocking population, escaping fish from nearby farms, and wild releases from fish keepers.
Keywords: Bengawan Solo River, diversity, ecosystem, fish, invasive